2022
DOI: 10.1002/hed.27200
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging‐based radiomics model for predicting radiation‐induced temporal lobe injury in nasopharyngeal carcinoma after intensity‐modulated radiotherapy

Abstract: Background To develop a model based on magnetic resonance imaging (MRI) radiomics and clinical features for predicting radiation‐induced temporal lobe injury (RTLI) in patients with nasopharyngeal carcinoma (NPC) after intensity‐modulated radiotherapy (IMRT). Methods Two hundred and sixteen patients with NPC were retrospectively included. Radiomics features were extracted and selected. The logistic regression analysis was performed for prediction models construction. The area under the receiver operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A recent genome-wide association study implicated the genetic susceptibility gene CEP128 in RTLI development ( 31 ). In the study by Bao et al ( 23 ), they found that T classification was the only independent clinical factor for the prediction of RTLI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent genome-wide association study implicated the genetic susceptibility gene CEP128 in RTLI development ( 31 ). In the study by Bao et al ( 23 ), they found that T classification was the only independent clinical factor for the prediction of RTLI.…”
Section: Discussionmentioning
confidence: 99%
“…It was constructed with only texture features extracted from T2WI. In a recent study, Bao et al ( 23 ) found that a radiomics–clinics model combining clinical T staging and radiomics features extracted from T2-weighted fat-suppressed and T1WI-CE showed a better predictive capability in RTLI than T staging alone and a single radiomics model. In this study, the texture features constructed radiomics and radiomics-clinics combined models were extracted from T1WI, T2WI, and T1WI-CE sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have tried their best to analyze the relationships between radiomics features and clinical outcomes, such as overall survival (OS) [ 35 ], local recurrence [ 24 ], and side effects after radiotherapy [ 36 ]. We focused on the risk of early distant metastasis and a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics turns the deep-seated feature information hidden in conventional medical images into quantitative data invisible to naked eyes (8,9). At present, there have been several studies that use MRI at different time points to construct radiomics models for predicting RTLI in NPC (10)(11)(12)(13)(14)(15)(16). Some studies have developed radiomics nomogram models based on MRI at the end of intensity modulated radiotherapy (IMRT) to predict the RTLI in NPC patients, and these models have shown outstanding predictive performance (11,13,15).…”
Section: Introductionmentioning
confidence: 99%